tapahtêyimisowin, mâtinamâtowak, wâhkôhtowin: Wise Practices in Teacher Education to Improve Outcomes for Indigenous Students ... - Loutitt, Shannon L.L. (University of Alberta Library, 2024)
Indigenous students deserve to feel a sense of holistic wellbeing and experience equitable educational outcomes, but Alberta’s K-12 education system is not currently meeting the needs of many of its First Nations, Métis, and Inuit students. Education should empower Indigenous students to achieve success as is understood by them and their families. While numerous systemic changes must take place to improve the holistic wellbeing and educational outcomes of Indigenous students, the role of teachers in students’ lives is central. Through a woven approach grounded in Indigenous methodologies, this paper answers the question: How should teacher educators approach professional learning for teachers in order to improve outcomes for Indigenous students? Teacher educators for pre-service and in-service teachers must begin with tapahtêyimisowin (humility), mâtinamâtowak (sharing), and wâhkôhtowin (relationship); these interconnected themes are rooted in Indigenous ways of knowing and provide a foundation from which to ...